[Banknot podziemny ze Zbigniewem Bujakiem] . Unofficial bank note with Zbigniew Bujak - Niezależny Bank Polski. (Niezależny Bank Polski, 1984)
Double-sided green and purple print on white paper. Banknote, with the portrait of Zbigniew Bujak (obverse) and the Gdańsk monument to the victims of the December 1970 street protests (reverse), resembles a Polish złoty (before 1995). Attributes of the banknote include: date of emission, statement of responsibility, the signatures of the director and the treasurer of emitting agency (in this case Solidarity and KOS). Denomination: 200 zł.